Social media motivations and political engagement among UTAR students - Lee, Yi Ling (2024)
Social media is used to fulfilled certain purposes. Young people are digital natives who use social media frequently, hence a lot of research has been done to examine the relationship—both direct and indirect—between their use of social media and political participation. Most of these studies tend to confirm to the findings of each other that there are direct and indirect relationships through mediating factors such as political knowledge. However, some scholars argue that social media use may not as impactful towards youths’ subsequent political engagement as proposed as youths use social media to gratify their certain needs. Applying Uses and Gratification theory (U&G Theory) and O-S-R-O-R model, this study attempts to explore the complex relationship between political involvement and social media motives among University Tunku Abdul Rahman (UTAR) students. The O-S- R-O-R model, a rational structure that integrates information, expression, and motivation, was frequently used in research to study how social media influences political engagement. The study employs quota sampling technique via survey method to collect data from a sample of 377 UTAR students to explore their motives in using social media. Findings show that social media need is the strongest motive in determining UTAR students’ political engagement, both directly and indirectly via mediating factors. Also, surprisingly, political knowledge tend to have a detrimental effect on their subsequent political engagement, which may be due to factors such as disillusionment which lead to discouragement as a result of deeper understanding. The research will help scholars and policymakers to understand and take advantage of these dynamics in adjusting strategy to involve more youths in politics.